Quality Test Study of Foam as an Indicator of Operational Readiness of ARFF Units in Aviation Safety - KOMALASARI, YETI; Muhammad Farhan Alfajri; Wahyudi Saputra (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2025)
The study aims to analyze the quality testing of foam at the ARFF (Airport Rescue And Firefighting) unit to ensure that it meets the foam requirements specified in PR 30 of 2022 and as a measure of operational readiness for ARFF in dealing with incidents or accidents involving fire. The research method used is descriptive qualitative, employing data collection techniques such as observation, interviews with five informants, documentation, and literature review. The research results include recommendations for proposing fire tests based on ICAO Doc 9137 for existing foam quality testing. Support for fire testing includes the availability of equipment and human resources from two responsible units, namely ARFF and Safety & Risk, through socialization and practical training. The implications of success through foam fire test quality testing support the operational readiness of ARFF in extinguishing fires resulting from incidents or accidents by achieving the foam capabilities required by PR 30 of 2022.